Honeybee Sentience: Scientific Evidence and Implications for EU Animal Welfare Policy - Roberto Bava; Giovanni Formato; Giovanna Liguori; Fabio Castagna (Veterinary Sciences, 2025)
The growing recognition of animal sentience has led to notable progress in European Union animal welfare legislation. However, a significant inconsistency remains: while mammals, birds, and cephalopods are legally protected as sentient beings, honeybees (Apis mellifera)—despite robust scientific evidence of their cognitive, emotional, and sensory complexity—are excluded from such protections. This manuscript examines, from an interdisciplinary perspective, the divergence between emerging evidence on invertebrate sentience and current EU legal frameworks. Honeybees and cephalopods serve as comparative case studies to assess inconsistencies in the criteria for legal recognition of sentience. Findings increasingly confirm that honeybees exhibit advanced cognitive functions, emotional states, and behavioral flexibility comparable to those of legally protected vertebrates. Their omission from welfare legislation lacks scientific justification and raises ethical and ecological concerns, especially given their central role in pollination and ecosystem stability. In general, we advocate for the inclusion of Apis mellifera in EU animal welfare policy. However, we are aware that there are also critical views on their introduction, which we address in a dedicated paragraph of the manuscript. For this reason, we advocate a gradual and evidence-based approach, guided by a permanent observatory, which could ensure that legislation evolves in parallel with scientific understanding, promoting ethical consistency, sustainable agriculture, and integrated health under the One Health framework. This approach would meet the concerns of consumers who consider well-being and respect for the environment as essential principles of breeding, and who carefully choose products from animals raised with systems that respect welfare, with indisputable economic advantages for the beekeeper.